2005
DOI: 10.2337/diabetes.54.11.3082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diabetes on Ryanodine Receptor Ca Release Channel (RyR2) and Ca2+ Homeostasis in Rat Heart

Abstract: The defects identified in the mechanical activity of the hearts from type 1 diabetic animals include alteration of Ca 2؉ signaling via changes in critical processes that regulate intracellular Ca 2؉ concentration. These defects result partially from a dysfunction of cardiac ryanodine receptor calcium release channel (RyR2). The present study was designed to determine whether the properties of the Ca 2؉ sparks might provide insight into the role of RyR2 in the altered Ca 2؉ signaling in cardiomyocytes from diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
167
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(185 citation statements)
references
References 49 publications
13
167
3
2
Order By: Relevance
“…This approach has abrogated the modulatory action of Ca 2+ transients on AP profile at different rates and has prevented the manifestation of destabilizing effects of spontaneous Ca 2+ releases on transmembrane potential. Enhanced diastolic Ca 2+ releases from the sarcoplasmic reticulum have been previously found in myocytes obtained from diabetic rats,67 suggesting that these spontaneous events may have contributed to the heterogeneity of electrical recovery observed in heart of STZ‐treated mice. Although these aspects represent important constraints to our study, we elected to initially dissect the contribution of ionic current remodeling on the electrical behavior of diabetic myocytes.…”
Section: Discussionmentioning
confidence: 88%
“…This approach has abrogated the modulatory action of Ca 2+ transients on AP profile at different rates and has prevented the manifestation of destabilizing effects of spontaneous Ca 2+ releases on transmembrane potential. Enhanced diastolic Ca 2+ releases from the sarcoplasmic reticulum have been previously found in myocytes obtained from diabetic rats,67 suggesting that these spontaneous events may have contributed to the heterogeneity of electrical recovery observed in heart of STZ‐treated mice. Although these aspects represent important constraints to our study, we elected to initially dissect the contribution of ionic current remodeling on the electrical behavior of diabetic myocytes.…”
Section: Discussionmentioning
confidence: 88%
“…Phosphorylation of RyR S2808 has been associated with increased RyR open probability and SR Ca 2ϩ leak due to dissociation of the stabilizing protein FKBP1B (16,29). Phosphorylation of RyR S2808 has been found especially high in the context of hyperglycemia and diabetes (30,38,39). A Zn 2ϩ -dependent reduction in S2808 phosphorylation and subsequent reduction in SR Ca 2ϩ leak could explain the enhanced sensitivity of the hyperglycemic prediabetic rat cardiomyocyte to the relaxing effects reduced IBa recorded at Ϫ20 mV in a reversible manner.…”
Section: Discussionmentioning
confidence: 99%
“…Although alteration of Ca 2ϩ signaling via changes in critical processes that regulate intracellular Ca 2ϩ has become a hallmark of this type of cardiomyopathy, controversies, currently going on, relate to specific alterations in Ca 2ϩ signaling pathways contributing to the cardiac defects in diabetes (7,20). Recently, we reported that these defects result partially from altered local Ca 2ϩ signaling due to a dysfunction of cardiac PKA-mediated ryanodine receptor Ca 2ϩ release channel (RyR2) (51).…”
mentioning
confidence: 99%
“…We and others have shown that chronic administration of ANG II receptor blockers could protect the heart from the development of cellular alterations typically related with diabetes (18,29,30,33,34). Although ANG II antagonism leads to an attenuation of the depressed SR-Ca 2ϩ -ATPase (SERCA) and to an improvement in intracellular Ca 2ϩ handling in heart failure (16,29), it is not known whether this antagonism can correct the defective interaction of RyR2 and FKBP12.6 that occurs in the SR during the development of diabetes-induced cardiomyopathy (51 …”
mentioning
confidence: 99%
See 1 more Smart Citation